Q - If \(f(x) = \displaystyle\int_1^x \dfrac{\ln t}{1 + t} \text{dt}\) where \(x > 0\) ,

Then the value of x satisfying the equation \( f(x) + f\left(\dfrac{1}{x}\right) = 2\) is

I attacked the question in this way,

\[ f(x) + f\left(\dfrac{1}{x}\right) = 2 \]

Differentiating both sides with respect to x.

\[ f'(x) + f'\left(\dfrac{1}{x}\right)\cdot \dfrac{-1}{x^2} = 0 \quad \quad ...1\]

Applying leibniz theorem in the given integral,

\[ f'(x) = \dfrac{\ln x}{1+x} \quad \quad f'\left(\dfrac{1}{x}\right) = \cfrac{\ln\left(\frac{1}{x}\right)}{1 + \frac{1}{x}} = \dfrac{-x \ln x}{1 + x}\]

Substituting values of \(f(x) \ and \ f'\left(\dfrac{1}{x}\right)\) in equation 1 ,

\[ \dfrac{\ln x}{1+x} = \dfrac{x \ln x}{1 + x} \]

\[\boxed{x = 1}\]

x = 1 is the wrong answer.Can you please help me out where i am wrong?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestThe error in your method is that you differentiated both sides of a non-identical equation. Only functions (implicit or explicit) and identities can be differentiated (this is one of the basic rules of differentiation).

The statement \(f(x)+f(1/x)=2\) is an equation in terms of \(x\) which holds true for a finite set of values of \(x\), i.e., the equality here is non-identical. As such, you can't differentiate it w.r.t \(x\).

The answers on this post highlights the fallacy of differentiating an equation which is not an identity.

Log in to reply

Thanks both of you.

Log in to reply

I think that you first need to look at the function \(g(x) = f(x) + f\left(\dfrac{1}{x}\right)\) in general.

Then \(g'(x) = f'(x) + f'\left(\dfrac{1}{x}\right)*\dfrac{-1}{x^{2}} = \dfrac{\ln(x)}{1 + x} + \dfrac{\ln(x)}{x(1 + x)} = \dfrac{x\ln{x} + \ln(x)}{x(1 + x)} = \dfrac{\ln(x)}{x}.\)

Integrate using the substitution \(u = \ln(x)\) to find that \(g(x) = \dfrac{1}{2}(\ln(x))^{2} + C.\)

Next, since \(g(1) = 0\) we see that \(C = 0,\) and so \(g(x) = \dfrac{1}{2}(\ln(x))^{2}.\)

Finally, for this to equal \(2\) we need to have \((\ln(x))^{2} = 4 \Longrightarrow \ln(x) = \pm 2,\)

and so either \(x = e^{2}\) or \(x = \dfrac{1}{e^{2}}.\)

Log in to reply

I really liked your solution,great observation that \(g(1) = 0\) .Thanks!

Log in to reply

akhil i am connected brillant now

Log in to reply

Good,sabse pehle mje apna phone number de..

Log in to reply

are you subscribed to brilliant

Log in to reply

Log in to reply

I am getting \(x=e^2\)

Log in to reply

Correct answer is \(e^2\) and \( e^{-2}\)

Log in to reply

@Brian Charlesworth , @Sandeep Bhardwaj , @Prasun Biswas , @Calvin Lin , @Pi Han Goh , @Tanishq Varshney , @Otto Bretscher , @Jon Haussmann

Log in to reply